Kostmann Syndrome With Neurological Abnormalities: A Case Report and Literature Review - Lyu, Baiyu; Lyu, Wei; Zhang, Xiaoying (Frontiers in Pediatrics, 2020)
Background: Severe congenital neutropenia (SCN), also known as Kostmann syndrome, is a rare heterogeneous group of diseases characterized by arrested neutrophil maturation in the bone marrow. Case Presentation: We report a case of Kostmann syndrome and review previously reported SCN cases with neurological abnormalities. A 10-year-old boy had a history of recurrent, once a month, infection starting at 6 months of age. He had neutropenia for more than 9 years, as well as intellectual disability. He was homozygous for the exon 3 c.430dupG mutation of the HAX1 gene NM-006118. After treatment of antibiotics and G-CSF, his symtoms were relieved and was 3 months free of infection. The search revealed 29 articles related to Kostmann syndrome caused by HAX1 gene mutation; they were screened, and the main clinical features of 13 cases of Kostmann syndrome with neurological abnormalities were summarized and analyzed. Conclusions: Kostmann syndrome has three main characteristics: severe neutropenia (<0.2 × 109/L), maturation arrest of granulopoiesis at the promyelocyte stage, and death due to infections. HAX1 gene mutations affecting both isoforms A and B are associated with additional neurological symptoms. G-CSF can improve and maintain neutrophil counts, and improve prognosis and quality of life. At present, hematopoietic stem cell transplantation is the only cure.